Thrombotic thrombocytopenic purpura in a 2.5-year-old boy with dengue infection: a rare complication. (2nd April 2020) - Gogireddy, Rajasekhar Reddy; Kumar, Vasanth; Ranjit, Suchitra; Natraj, Rajeswari; Venkatachalapathy, Priyavarthini; Jayakumar, Indira; Margabandhu, Saravanan
ABSTRACT: Acute kidney injury (AKI) is a neglected and least studied complication of dengue. AKI secondary to thrombotic thrombocytopenic purpura (TTP) in dengue is extremely rare and there are few case reports. A 2.5-year-old boy with dengue who developed TTP in the critical phase of illness is described. He presented with microangiopathic haemolysis, thrombocytopenia and AKI. Haemolytic uraemic syndrome (HUS)/TTP was suspected and he underwent seven cycles of plasma exchange along with renal replacement therapy, following which he made a complete recovery. Prompt recognition of renal complications in dengue fever and early initiation of appropriate renal replacement therapy along with plasma exchange are essential for a good outcome. Abbreviations : AKI, acute kidney injury; GCS, Glasgow coma scale; HUS, haemolytic uraemic syndrome; LDH, lactate dehydrogenase; NS1, non-structural protein 1; pRIFLE, paediatric risk, injury, failure, loss, end-stage renal disease; SLED, sustained low-efficiency dialysis; TMA, thrombotic microangiopathy; TTP, thrombotic thrombocytopenic purpura.